Pengaruh Online Review terhadap Keputusan Pembelian di Restoran Waroeng Kampoeng Jimbaran Bali - Vanessa, Patricia; Suarka, Fanny Maharani; Sulistyawati, Agung Sri (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
Restaurant is a business in the catering service sector that provides services for ordering food and beverages. Over time, the development of the internet is increasingly felt and tourists can easily get the information they want from the internet. Reviews on the internet are one of the things that has the potential to influence their perception of a place, especially a restaurant. In recent years, there have been many sources of data information on the internet that can influence readers with reviews of their experiences. Google Reviews, Zomato and Tripadvisor are some of the sites that are quite widely used by tourists. Therefore, in this study, the authors examined the effect of online reviews on purchasing decisions at Waroeng Kampoeng Jimbaran Bali Restaurant. The restaurant that the author studied is the Waroeng Kampoeng Restaurant which is located in the Jimbaran area, Bali. In this study using qualitative as well as quantitative data, and the determination of informants and samples was carried out by purposive sampling method. Based on the results of statistical tests obtained from the simple linear regression equation, the results obtained Y = (4.463) + 0.732X with a correlation result of 0.732, which means it has a